Extreme Power Point Tracking to Yield Maximum Power in Solar Grid System - Seshi Reddy, D; S.S.susmitha, G; Yamini, N; Yashwanth, N (International Journal of Engineering and Technology, 2018)
To minimize power losses by limiting maximum feed-in power in a PV system. By this, we can get a stable powergenerationoperation. There are currently two types of charge controllers commonly used in Solar PV grid connected power system, (i) PWM (pulse width modulation) & MPPT (Maximum Power Point Tracking). Present solar inverter are not performing good yielding for wide range of irradiance and temperature. In this paper, MPPT adoption target to improve the performance when solar cell temperature varies from moderate to maximum from 450C to 750C. We used modified Perturb and Observation P&O MPPT technique, because it modifies the operating voltage or current of PV panel until we get maximum power extraction at wide range of operating conditions. Another technique opted in this paper, PWM charge controller is a good low cost solution for small capacity inverters only. In DC - DC converter switching strategy such that optimizes charge distribution between the battery bank or utility grid. In this we use only voltage sensor at PV array along with irradiance and temperature inputs and same had simulated in MATLAb2017a environment. The results obtained are satisfactory with consistant performance for wide range of temperature.Â Â